Strange nature : the insect portraits of Levon Biss - Mone, Gregory; Biss, Levon (2021)
"Adapted from the adult title Microsculpture, this book for young readers is a unique photographic study of insects in mind-blowing magnification that celebrates the wonders of nature and science. Levon Biss's photographs capture in breathtaking detail the beauty of the insect world and are printed in large-scale formats to provide an unforgettable viewing experience"--
From the collections of the Oxford University Museum of Natural History.
Includes bibliographical references and index.
Ages 8 to 12
Keywords: Insects -- Pictorial works; Photography of insects